Constraints Faced by Farmers and Extension Personnel of Dimapur District of Nagaland in the use of Icts While Enterprising Agriculture and Allied Activities - Sumi, Ditolyn; Singh, Rajkumar Josmee (Indian Journal of Hill Farming, 2018)
The main constraints faced by farmer in using ICTs on enterprising agriculture and allied activities were: The ‘Lack of awareness about different sources of information’ followed by ‘Privation of proper education facilities’, ‘Insufficient regional specific information & expatriate language’, ‘Lack of knowledge & skill in operating ICTs’, ‘Complexity in using ICTs’, ‘Poor socio-economic status’, ‘Poor network and low internet accesses’, ‘Negative attitude towards ICTs’, and ‘Erratic power supply’ were the constraints faced by farmers in use of ICTs. The major constraints faced by extension personnel in using ICTs while providing agro-advisory services were: ‘Inadequate accessibility to internet facilities’, ‘Inadequate infrastructure’, ‘Poor mobile phone network signal’, ‘Lack of ICT projects or initiatives’, and ‘Erratic power supply’.